1993
DOI: 10.1002/j.2161-0045.1993.tb00434.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Distress and Counseling Duration of Career and Noncareer Clients

Abstract: This study compared the presenting psychological symptom status and the counseling duration of career and noncareer clients. Although no significant differences in the psychological status of the two groups were noticed, career clients did attend significantly fewer counseling sessions than did clients with noncareer concerns. Implications of these findings for college counseling centers are offered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 14 publications
2
12
0
Order By: Relevance
“…A limited number of studies are devoted to the exploration of the overlap of career and personal/mental health counseling (Gold, & Scanlon, 1993; Niles et al, 2000; Pace & Quinn, 2000; Spengler, 2000). This study addressed this concern by demonstrating the interconnectednessof career concerns and mental health diagnoses.…”
Section: Resultsmentioning
confidence: 99%
“…A limited number of studies are devoted to the exploration of the overlap of career and personal/mental health counseling (Gold, & Scanlon, 1993; Niles et al, 2000; Pace & Quinn, 2000; Spengler, 2000). This study addressed this concern by demonstrating the interconnectednessof career concerns and mental health diagnoses.…”
Section: Resultsmentioning
confidence: 99%
“…Research has consistently revealed that most clients will attend less than six sessions, with a median length of 3-4 sessions (Draper et al 2002;Gallagher 2002;Garfield 1994;Gold and Scanlon 1993;Howard et al 1989;Koss 1979;Lambert et al 2001;Ledsky et al 2000;Scogin et al 1986;Vermeersch et al 2004;Ward and McCollum 2005). Furthermore, the modal duration for counseling or psychotherapy is one session, something experienced by as many as 50% of clients (cf., Anderson and Lambert 2001;Pekarik 1996;Talmon 1990;Wolgast et al 2003).…”
Section: Initial Counseling Stagementioning
confidence: 95%
“…He found that students who presented for personal counseling scored significantly higher than control participants on both Al and Di. Gold and Scanlon (1994) studied the differences between students who presented for personal counseling and those who presented for vocational or educational counseling. They found no differences between career and noncareer clients.…”
Section: Young Adults Of College Agementioning
confidence: 99%